Mechanical properties and thermal stability of poly (L-lactic acid) treated by Co-60 gamma radiation - Tran , Minh Quynh; Nguyen , Van Binh; Pham , Duy Duong; Hoang , Phuong Thao; Pham , Ngoc Lan; Le , Thi Mai Linh (Nuclear Science and Technology, 2013)
Poly (L-lactic acid) (PLLA) was mixed with 5 wt% polyethylene glycol 1000 g.mol-1 (PEG) as a plasticizer and 3 wt% triallyl isocyanurate (TAIC) as a crosslinking agent for preparation of the plasticized PLLA films. The crosslinking plasticized materials were prepared from the plasticized PLLA by irradiation with various radiation doses under the Cobalt-60 gamma radiation source at Hanoi Irradiation Center. The crosslinking structures were introduced in different formulations of PLLA, and the crosslinking density increased with radiation dose and seemed to be saturated at 50 kGy. The resulting stable crosslinking network inhibited the mobility for crystallization of PLLA chains. As a result, thermal stability of the crosslinking plasticized PLLA increased, and the plasticized PLLA crosslinked with TAIC at 50 kGy become much higher than that of initial PLLA with a very small endothermic peak at its melting temperature in the DSC thermogram. The stress-strain curves of the crosslinking plasticized PLLA showed the toughness of the materials reduced but still higher than that of initial PLLA, whereas its tensile strength was much improved by radiation crosslinking.